A craniometric and genetic approach to the systematics of the genus Dasymys PETERS, 1875 and the description of three new taxa (Rodentia, Muridae, Africa) - (:unkn) unknown (My University, 2003)
In an attempt to properly identify Dasymys specimens that were collected during the last decennia in the East-African region (Rwanda-Tanzania) we undertook a revision, of this genus. Although we initially limited our study area to central and eastern Africa, we were forced to include specimens for comparison from other areas, including western Africa, Angola and Zimbabwe-Zambia. This revision was realized using craniometric data of nearly 1000 skulls grouped in 20 operational taxonomical units (OTU's) mainly occurring in the central and eastern part of the African continent. The observation that differences in age and sex composition of the OTU's are of no or little consequence for the branching of the obtained phenetic trees, allowed us to undertake the screening of the genus Dasymys of the central and eastern African region. This approach enabled us to evaluate already described taxa, to select a neotype for D. nudipes and to describe three new taxa. Subsequent genetic analysis (cytochrome b) allowed us to provide a genetical characterization of two of the new species and several other taxa. Our phylogenetic analysis suggests that the genus Dasymys originated in the west African forest block betore spreading in a first step to the forest of the central African region and then in a second step to the savannahs of southern, eastern and possibly also western Africa.
Keywords: African Research